EFEKTIVITAS MEDIA 2D DAN 3D SEBAGAI EDUKASI GIZI TERHADAP PENGETAHUAN ANAK SEKOLAH DASAR - oktaviani, raden puspa; Kurniasari, Ratih (Peneliti.net, 2024)
Media education is carried out using a variety of media, there are two-dimensional, three-dimensional and innovative media such as games. Interesting media can make responsiveness to increasing children's knowledge more effective, there are colors, images with designs that create attraction so that they become interested in reading. The purpose of the literature review is to determine the effectiveness of 2-dimensional and 3-dimensional educational media on increasing knowledge in elementary school children. The method used to review journals as a source of data with a population of elementary school children the sample is mostly taken in the research of 4th and 5th grade elementary school students with various research instruments such as questionnaires, 2-dimensional and 3-dimensional media and measuring tools for height and weight. The results of the study there was an increase in knowledge by using various 2-dimensional and 3-dimensional media. The advantages of using media that have an appeal so that the delivery and receipt of information can be easily found in elementary school children.